MiR34a Regulates Neuronal MHC Class I Molecules and Promotes Primary Hippocampal Neuron Dendritic Growth and Branching - Hu, Yue; Pei, Wenqin; Hu, Ying; Li, Ping; Sun, Chen; Du, Jiawei; Zhang, Ying; Miao, Fengqin; Zhang, Aifeng; Shen, Yuqing; Zhang, Jianqiong (Frontiers in Cellular Neuroscience, 2020)
In the immune system, Major Histocompatibility Complex class Ⅰ (MHC-I) molecules are located on the surface of most nucleated cells in vertebrates where they mediate immune responses. Accumulating evidence indicates that MHC-I molecules are also expressed in the central nervous system (CNS) where they play important roles that are significantly different from their immune functions. Classical MHC-I molecules are temporally and spatially expressed in the developing and adult CNS, where they participate in synaptic formation, remodeling and plasticity. Therefore, clarifying the regulation of MHC-I expression is necessary to develop an accurate understanding of its function in the CNS. Here, we show that microRNA 34a (miR34a), a brain enriched noncoding RNA, is temporally expressed in developing hippocampal neurons, and its expression is significantly increased after MHC-I protein abundance is decreased in the hippocampus. Computational algorithms identify putative miR34a target sites in the 3’UTR of MHC-I mRNA, and here we demonstrate direct targeting of miR34a to MHC-I mRNA using a dual luciferase reporter assay system. MiR34a targeting can decrease constitutive MHC-I expression in both Neuro-2a neuroblastoma cells and primary hippocampal neurons. Finally, miR34a mediated reduction of MHC-I results in increased dendritic growth and branching in cultured hippocampal neurons. Taken together, our findings identify miR34a as a novel regulator of MHC-I for shaping neural morphology in developing hippocampal neurons.